Pengaruh Penggunaan KNO3 pada Pertumbuhan Bibit Kelapa Sawit (Elaeis guineensis Jack) Fase Pre-Nursery - Kresna Shifa Usodri; Bambang Utoyo (Kadiri University, 2021)
Fulfillment of quality seeds in the effort of increasing oil palm productivity can be done by means of appropriate fertilization. One of the fertilizers that can be used to optimize seedling growth in the pre-nursery is by using KNO3. The objective of this research was to find out KNO3 concentration in optimizing the growth of oil palm seedlings in the prenursery phase. The research was conducted in the Oil Palm Nursery Unit of Politenik Negeri Lampung. The experimental design used was a single treatment with five replications. The treatments consisted of the recommended compound NPK fertilizer (P1), 1% concentration of KNO3 fertilizer (P2), 2% concentration of KNO3 fertilizer (P3), 3% concentration of KNO3 fertilizer (P4), and 4% concentration of KNO3 fertilizer (P5). Once the results of analysis of variance was significant, the analysis was proceeded with the least significant difference test (LSD) at significance level of 5%. The results showed that the application of KNO3 had a significant effect on the growth of oil palm seedlings in the pre-nursery phase. Application of KNO3 fertilizer with a concentration of 4% (P5) showed higher growth yields than other treatments in the pre-nursery phase of oil palm seedlings.Pemenuhan bibit berkualitas dalam upaya peningkatan produktivitas kelapa sawit, dapat dilakukan dengan cara pemilihan jenis pupuk yang sesuai. Salah satu pupuk yang dapat digunakan dalam mengoptimalkan pertumbuhan bibit di pre-nursery adalah dengan menggunakan KNO3. Penelitian dilakukan dengan tujuan untuk mendapatkan konsentrasi pupuk KNO3 yang tepat dalam mengoptimalkan pertumbuhan bibit tanaman kelapa sawit pada fase pre-nursery. Penelitian dilakukan di Unit Pembibitan Kelapa Sawit, Politenik Negeri Lampung. Rancangan percobaan yang digunakan adalah perlakuan tunggal dengan lima ulangan. Perlakuan terdiri dari pupuk NPK majemuk anjuran (P1), pupuk KNO3 konsentrasi 1% (P2), pupuk KNO3 konsentrasi 2% (P3), pupuk KNO3 konsentrasi 3% (P4), dan pupuk KNO3 konsentrasi 4% (P5). Apabila hasil dari analisis ragam signifikan, maka pengujian data dilanjutkan dengan Uji Beda Nyata Terkecil (BNT) pada taraf 5%. Hasil penelitian menunjukkan aplikasi KNO3 berpengaruh nyata terhadap pertumbuhan bibit kelapa sawit pada fase pre-nursery. Pemberian pupuk KNO3 dengan konsentrasi 4% (P5) menunjukkan hasil pertumbuhan bibit yang lebih optimal dibandingkan dengan perlakuan lainnya pada fase pre-nursery